Identification and differential analysis of noncoding RNAs in response to drought in Phyllostachys aureosulcata f. spectabilis - Yang, Yang; Gao, Yuanmeng; Li, Yiqian; Li, Xueping (Frontiers in Plant Science, 2022)
The role of noncoding RNAs (ncRNAs) in plant resistance to abiotic stresses is increasingly being discovered. Drought stress is one of the most common abiotic stresses encountered and has a deep impact. In this study, high-throughput sequencing was performed on plant tissue samples from 0, 2, 4 and 6 days of drought treatment Phyllostachys aureosulcata f. spectabilis C. D. Chu et C. S. Chao, and the sequencing results were analysed bioinformatically. We detected 336,946 ncRNAs among all 12 samples, including 192,098 message RNAs (mRNAs), 142,761 long noncoding RNAs (lncRNAs), 1,670 circular RNAs (circRNAs), and 417 microRNAs (miRNAs). We detected 15,015 differentially expressed (DE) ncRNAs, including 436 DE circRNAs, 14347 DE lncRNAs and 232 DE miRNAs. Then, we used Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) to functionally predict DE ncRNAs. The results showed that most DE ncRNAs are involved in the response to drought stress, mainly in biochemical reactions involved in some metabolites, as well as in organelle activities. In addition, we validated two random circRNAs and demonstrated their circularity. We also found a stable internal reference gene available for goldenrod and validated the accuracy of this experiment by quantitative real-time polymerase chain reaction (qRT-PCR).